Corporate Governance in Organizations of Higher and Postgraduate Education as Leverage Point for Pathways to the Tourism Development - ISMURATOV, Daniyar; KUSHEBINA, Gulnar; VALIYEVA, Saltanat; MANGIBAYEVA, Dina (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The purpose of this study is to analyze corporate governance in higher and postgraduate educational institutions and its impact on the development of tourism, under the conditions of globalization changes taking place around the world. Applying a research methodology lens, we identified main priority points for intervention (leverage points) which appear to be a key for the decisional factors which aimed to boost development of tourism through transformative changes initiated by the government, business, civil society and academia.